2021
DOI: 10.1097/acm.0000000000004150
|View full text |Cite
|
Sign up to set email alerts
|

Use of Generalizability Theory for Exploring Reliability of and Sources of Variance in Assessment of Technical Skills: A Systematic Review and Meta-Analysis

Abstract: Purpose Competency-based education relies on the validity and reliability of assessment scores. Generalizability (G) theory is well suited to explore the reliability of assessment tools in medical education but has only been applied to a limited extent. This study aimed to systematically review the literature using G-theory to explore the reliability of structured assessment of medical and surgical technical skills and to assess the relative contributions of different factors to variance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…This was confirmed by the generalizability analysis, which showed that disagreement between assessors only accounted for 0.8% of the variance despite minimal rater training. 22 This positive finding suggests that the tool is easy and unambiguous to use.…”
Section: Discussionmentioning
confidence: 97%
“…This was confirmed by the generalizability analysis, which showed that disagreement between assessors only accounted for 0.8% of the variance despite minimal rater training. 22 This positive finding suggests that the tool is easy and unambiguous to use.…”
Section: Discussionmentioning
confidence: 97%
“…We used G theory to explore the relative contributions to the assessments' variance, 10 as recommended in modern reliability research 10,26 . In contrast to the modest level of reliability found using κ analysis, G analyses demonstrated a very high G coefficient (>0.8) 22 with most of the variance being attributed to participant performance (ie, true variance).…”
Section: Discussionmentioning
confidence: 99%
“…This absolute coefficient was chosen because the scores contributing to each student’s grade point average (GPAX) were based on predefined criteria, not relative comparison. The established lower limit for reliability (Phi-coefficient) was 0.70 for formative examination and 0.80 for summative examination, which signified high generalizability of assessment scores [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%